Higher Losses and Slower Development in the Absence of Disaster Risk Management Investments - Hallegatte, Stephane; Bangalore, Mook; Jouanjean, Marie-Agnes (World Bank, Washington, DC, 2016)
Global economic losses from natural disasters continue to increase. Yet, investments in disaster risk management are not universal, as they are traditionally seen as in competition with other development and economic priorities. The multitude of benefits from disaster risk management investments are not traditionally accounted for in cost-benefit analyses. This paper contributes to this discussion by highlighting the multiple benefits from disaster risk management investments, focusing on the avoided losses when a disaster occurs, but also on the impacts on economic development even before a disaster strikes. The paper's main message is that disaster risk management investments can provide two dividends: reduced losses when a disaster strikes, and a shift of investment strategies and perhaps even an increase in investment value that would benefit the economy even before a disaster strikes. Providing evidence to policy makers and investors about the existence of both types of dividends can provide a narrative reconciling short-term and long-term objectives, thereby improving the acceptability and feasibility of disaster risk management investments.